The Relationship Of Knowledge And Attitude Of Mothers Of Newborn Babies Regarding Congenital Hypothyroid (SHK) Screening At Kayu Laut Health Center, Panyabungan Selatan District Christmas Mandiling - Dewi Srirahayu Tinendung; Khoirunnisa’a Batubara (Sean Institute, 2021)
Congenital Hypothyroidism Screening, for short, is a screening to select babies who suffer from Congenital Hypothyroidism (HK) from babies who are not sufferers. All babies born in Indonesia must be screened for Congenital Hypothyroidism (SHK) to detect if there is a risk of abnormalities in the child's growth and development. The aim of this study was to determine the relationship between knowledge and attitudes of mothers of newborns regarding Congenital Hypothyroidism Screening (SHK). This type of research uses quantitative research with correlational methods. The population in this study was 41 mothers who had newborn babies. The sampling method in this research used total sampling. Data collection uses a questionnaire. Data analysis used the chi square test. The results of the analysis show that the analysis of the relationship between knowledge and attitudes of mothers of newborns regarding Congenital Hypothyroid Screening (SHK) showed that of the 7 respondents who had good knowledge about SHK, all 7 people (17.1%) had positive attitudes. quite a majority had a positive attitude as many as 18 people (43.9%). Meanwhile, of the 12 respondents who had less knowledge, 8 people (19.5%) had a negative attitude. The results of the chi-square statistical test prove that there is a significant relationship between the knowledge and attitudes of mothers of newborns regarding Congenital Hypothyroidism (SHK) Screening at the Kayu Laut Community Health Center, Panyabungan Selatan District, Mandailing Natal Regency, with p value = 0.002 (p<0.05).